Review: Use of Asian samples in genetic research of alcohol use disorders: Genetic variation of alcohol metabolizing enzymes and the effects of acetaldehyde. (18th January 2017) - Matsushita, Sachio; Higuchi, Susumu
Abstract : Background and Objectives: Epidemiological studies consistently find that Asian populations report lower rates of alcohol use disorders (AUD) compared with other racial groups. These differences result from a variety of biological, genetic, and environmental influences, some of which are related to the metabolism of alcohol. We will review several studies of these metabolic factors, including several alcohol clamping studies conducted in our laboratory, that provide further insight into the role of the alcohol metabolizing genes and drinking behavior among Japanese drinkers. Methods: This manuscript reviewed studies investigating genetic variations of alcohol metabolizing enzymes among Asians and several mechanisms by which these genes are thought to give rise to differences in rates of alcohol dependence. Results: The inactive aldehyde dehydrogenase 2 ( ALDH2 ) and highly active alcohol dehydrogenase‐1B ( ADH1B ) genes are protective factors for the development of AUD. The inactive ALDH2 provides its protective effect through the accumulation of acetaldehyde after consuming alcohol, resulting in unpleasant effects, and heightened sensitivity to alcohol. However, the suppressive effects of inactive ALDH2 and highly active ADH1B for AUDs are only partial and interact with other factors, such as personality traits, psychiatric comorbidities, and environmental factors. Discussion and Conclusions: While Asians are excellent models for the study of certain genetic effects on the development and consequences of AUD, few clinical studies of this population have been conducted. Further exploration of the interactions between various genetic, individual, and environmental factors influencing drinking behavior and, thus affecting the risk of AUD, would enhance our understanding of how alcohol‐related problems develop. Scientific Significance: The heterozygous ALDH2*1/*2 genotype has only partial effects on limiting drinking behavior, suggesting the potential interaction with other factors. Therefore AUD patients with inactive ALDH2 may be a useful model to identify and to test a variety of other risk factors of AUD. (Am J Addict 2017;26:469–476)